Project Based Learning (PLO) with a Bio-Entrepreneurship (BEP) Approach: Can it Improve Students' Science Literacy and Life Skills? - Priadi, Median Agus; T. Marpaung, Rini Rita; Azhari, Azhari; Innayah, Nabila Alifia (Biosfer: Jurnal Tadris Biologi, 2024)
This research aims to analyze the PjBL model with the Bio-Entrepreneurship (BEP) approach to scientific literacy abilities and life skills. The method used was quasi-experimental with a pretest posttest non-equivalent control group research design. The sample for this research consisted of 71 students consisting of experimental classes and control classes, using a purposive sampling technique. The results of research on scientific literacy abilities show that the average N-Gain in the experimental class is 0.67 with medium criteria, while the control class average N-Gain is 0.28 with low criteria. The results of life skill abilities after being given treatment in the experimental class increased higher with an average of 78.63 compared to those in the control class with an average of 51.74. Thus, this research shows significant implications for students' abilities in developing real projects by combining aspects of entrepreneurship and biological concepts in everyday life.ABSTRAK: This study aims to analyze the PjBL model with a Bio-Entrepreneurship (BEP) approach to science literacy and life skills. The method used was quasi experiment with pretest posttest nonequivalent control group design. The sample of this study amounted to 71 students consisting of experimental and control classes, with purposive sampling technique. The results of the research on science literacy skills showed that the average N-Gain in the experimental class was 0.67 with moderate criteria, while the control class had an average N-Gain of 0.28 with low criteria. The results of life skills ability after being treated in the experimental class increased higher with an average of 78.63 than in the control class with an average of 51.74. Thus, this research shows significant implications for the ability of students to develop real projects by combining entrepreneurial aspects and biological concepts in everyday life.